2019
DOI: 10.1088/1361-6528/ab5a0a
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic treatment of periodic gold nanowire array nanofasteners under shear loading

Abstract: Comprehensive molecular dynamics simulations are conducted to unravel the mechanics and mechanisms associated with the strength and fracture behavior of a highly ordered gold nanowire (Au-NW) array of a pair of nanofasteners (nanoconnectors) under externally applied shear strain. Large-scale atomic/molecular massively parallel simulator (LAMMPS and embedded atom method were adopted to model the atomic interactions of a number of neighboring nanofasteners. This was affected via the use of a periodic simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The as-created MD geometry consists of two cylindrical nanocrystals that are separated one lattice constant away side-by-side. As previously demonstrated, the mechanical performance of the bonded nanocrystal pair is not sensitive to the separation distance as long as it is sufficient for contact [34,37]. The original coldwelding approach for individual nanowires as proposed by Lu et al [1] did not require applying current or external force.…”
Section: Simulation Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The as-created MD geometry consists of two cylindrical nanocrystals that are separated one lattice constant away side-by-side. As previously demonstrated, the mechanical performance of the bonded nanocrystal pair is not sensitive to the separation distance as long as it is sufficient for contact [34,37]. The original coldwelding approach for individual nanowires as proposed by Lu et al [1] did not require applying current or external force.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…In recent years, atomistic simulations have been widely used as a powerful tool to investigate all kinds of structural performance regarding various nanostructures [23][24][25][26][27][28][29][30][31][32][33][34]. Our atomistic simulations here are conducted by using the software package LAMMPS [35].…”
Section: Simulation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the van der Waals attraction transmitted through the connecting surface results in the size effect of the cold-welded nanocrystals. Besides 1D nanowires, the cold welding technique can also be used in complex nano-systems, such as nano-fasteners, 10 nanoribbons, 11 nanocomposites, 12 nano-assemblies, 13 and nanoporous materials. 14…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the van der Waals attraction transmitted through the connecting surface results in the size effect of the cold-welded nanocrystals. Besides 1D nanowires, the cold welding technique can also be used in complex nano-systems, such as nano-fasteners, 10 nanoribbons, 11 nanocomposites, 12 nano-assemblies, 13 and nanoporous materials. 14 Amorphous alloys lack atomic arrangement with long-range order and, thus, exhibit high strength, high elasticity, superior soft magnetic properties, and outstanding corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%